2023
DOI: 10.1109/tcpmt.2023.3293003
|View full text |Cite
|
Sign up to set email alerts
|

On the Fast Prediction of the Aerodynamic Performance of Electronics Cooling Fans Considering the Effect of Tip Clearance

Abstract: This study aims to complete and validate a recently developed reduced-order model for the fast prediction of aerodynamic performance (P -Q) curve of electronics cooling fans, taking into account the real fan geometry and the tip clearance effect. The effect of tip clearance on tip vortex generation and fan performance was revealed by an experimentally validated 3D computational fluid dynamics (CFD) method. Six different tip clearance ratios ranging from 0% to 12.7% were investigated. The tip clearance was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…These mechanisms regulate the fan speed based on the temperature of the GPU, ensuring that the fan runs at an optimum speed to ensure optimal cooling without making too much noise. According to Zhao et al, altering the design of the fan blades can also improve the heat dissipation property of fans [49].…”
Section: Cooling Fansmentioning
confidence: 99%
“…These mechanisms regulate the fan speed based on the temperature of the GPU, ensuring that the fan runs at an optimum speed to ensure optimal cooling without making too much noise. According to Zhao et al, altering the design of the fan blades can also improve the heat dissipation property of fans [49].…”
Section: Cooling Fansmentioning
confidence: 99%
“…The aeroacoustic characteristics of cooling fans are determined by their aerodynamics, such as flow separation, secondary flow and other special flow structures. A large number of studies have been performed on aerodynamic characteristics [3][4][5][6][7][8][9] and aeroacoustic characteristics [10][11][12][13][14][15][16]. For example, Nashimoto et al [3] used phase-averaged PIV measurement and found that the separation and reattachment of the flow occurred on the suction surface at the leading edge of the blade.…”
Section: Introductionmentioning
confidence: 99%
“…Bo et al [5] found that there is leakage flow in the tip clearance and high-velocity region on the suction side near the blade tip. Zhao et al [6] compared the vortex strength of the blade tips with different tip clearances and found that the proximity of a shroud mitigates tip vortices. Mo et al [10] found that there is a strong tonal noise at the leading edge of the blades with a high sound pressure level (SPL).…”
Section: Introductionmentioning
confidence: 99%